Determination of Some Trace Metals in Cobwebs as Indoor Pollutants in Modibbo Adama University of Technology Yola, Adamawa State, Nigeria - O N, Maitera; S, Ishaku; A B, Abubakar (International Journal of Chemistry and Materials Research, 2022)
This study aimed at assessing the trace metals contents of cobwebs using atomic absorption spectroscopy. The cobwebs were collected from male’s hostel; females hostel, chemistry laboratory, and lecture theatre areas in order to establish the level of suspended trace metals in the atmosphere. The cobwebs were digested with aqua regia before analysis using atomic absorption spectrophotometer (AAS). The highest concentration value of Fe, Mn, Zn, Cu, Pb, Co, Cd, Na, and Mg are 10.388±4.734, 4.228±3.267, 0.461±0.900, 0.639±0,529, 0.13±0.05, 0.115±0.099, 0.004±0.001, 0.600±0.400, and 0.015±0.035 mg/L respectively, from MH, FH, CL, and LT. It was found that, the concentration of trace metals in cobwebs decreases as the harmattan, burning of dumpsite, and school activities decrease. In general, the total concentration of all elements varied from 10.388 mg/L assessed at male hostel (MH) to 0.002 mg/L at lecture theatre (LT). The values recorded for all the element may be due to the use of cosmetic; dust, heating equipment (stoves, heater, fireplaces), paint, burning of refuses, vehicle emission, insecticide or pesticides usage, tobacco smoke around the study area. The fact that appreciable values of trace metals were recorded in the study area affirmed the presence of unsafe air in the institution. Therefore, there is a need not only to curb activities that increase these trace metals, but also to ensure perennial brooming and removing cobwebs dusts in the institution.